Pengaruh Modul Elektronik Audio-VisualTerhadap Motivasi Berwirausaha dan Hasil Belajar Mahasiswa - Ninik Sudarwati; Masruchan; Nur Iffah; Dewi Urip Wahyuni; Deni Widyo Prasetyo (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this study is to examine the entrepreneurial motivation of students who use the audio-visual e-module as a learning resource by utilization, the effect of using the audio-visual e-module on managing the business as a learning resource by utilization with learning outcomes, and the impact of entrepreneurial motivation on managing learning outcomes. By utilizing student entrepreneurial practice learning outcomes, a business can be used as a source of learning. Quantitative methods with questionnaires and tests were used to analyze the data. The research subjects were 50 students consisting of 25 control class students and 25 experimental class students. Linear Regression Test Technique using SPSS version 24 is used to determine the effect of student entrepreneurship motivation with student learning outcomes. This study concludes that (1) the entrepreneurial motivation of students using the audio-visual e-module to manage their business as a learning resource is in the very good category; (2) There is a significant influence from the use of the audio-visual e-module in managing the business as a learning resource; (3) There is a significant effect between the entrepreneurial motivation of students who use the audio-visual e-module to manage their business as a learning resource and their utilization of the learning outcomes of entrepreneurial practices. The findings of this study have implications for the discovery that the audio-visual electronic module on business management as a relevant learning resource is applied to learning Entrepreneurship courses.